Time period after transcatheter PDA closure with changes in left ventricular function and nutritional status - Muhammad Irfan; Muhammad Ali; Tina Christina Lumban Tobing; Wisman Dalimunthe; Rizky Adriansyah (Indonesian Pediatric Society, 2021)
Background Few studies perform follow ups on patent ductus arteriosus (PDA) patients who undergo transcatheter closure. In addition to side effects from the procedure, it is important to evaluate changes in left ventricular function (LVF) parameters and nutritional status. Objective To compare LVF and nutritional status before and during the one-year period post-transcatheter PDA closure, and evaluate potential associated factors in post-closure PDA transcatheter patients. Methods This retrospective cohort study was done in a single center in patients diagnosed with PDA who had undergone transcatheter closure. Data were obtained from subjects’ medical records. The relationship between the post-closure PDA time span and LVF parameters [ejection fraction (EF) and fractional shortening (FS)] was analyzed by Friedman and repeated ANOVA tests; the post-closure PDA time period and nutritional status was analyzed by Friedman test. The time periods analyzed were 1, 3, 6, and 12 months post-closure. Factors potentially associated with LVF 12 months post-closure were analyzed by linear regression. Results A total of 30 patients who had undergone transcatheter PDA closure were included. The body weight mean of at the time of transcatheter PDA closure was 13.1 kg. We found a significant relationship between time period after PDA closure and nutritional status, before and 1, 3, 6, and at 12 months post-closure. In a comparison of pre-closure to 12 months post-closure, subjects’ mean EF (66.6 vs. 70.9%, respectively; P<0.001) and FS (34.4 vs. 37.8%, respectively; P<0.001) were significantly higher. In addition, significantly more patients had normal nutritional status 12 months post-closure than before closure. Age was not related to LVF parameters (EF: r=0.212; P=0.260; FS: r=0.137; P=0.471). Conclusion Both LVF and nutritional status significantly improve gradually over the 12 months post-closure compared to pre-closure. PDA size is not significantly associated with improved LVF parameters and nutritional status.